26. SURVEY ON THE SINGLE AND COMBINED PHYSICAL CONSTITUTIONS ACCORDING TO TRADITIONAL MEDICINE AMONG (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the distribution of traditional Chinese medicine body constitution types - including single, combined constitutions - among students of the University of Medicine and Pharmacy at Ho Chi Minh city, and to identify the predominant constitution patterns.Subjects and methods: A cross-sectional study was conducted on 798 University of Medicine and Pharmacy at Ho Chi Minh students in 2025. Participants were assessed using the constitution in Chinese medicine questionnaire to classify their single traditional Chinese medicine constitution type and combined constitution if present.Results: The mean age of participants was 21.65 years (female-to-male ratio: 5.9:1). First-year students had the highest participation rate at 23.56%, while second-year students had the lowest at 14.16%. Among single constitutions, which made up 34.2%, the most common was Neutral at 37.7%, followed by Qi-deficiency at 21.6%; the least common was Phlegm-Dampness at 0.7%. Mixed constitutions accounted for 65.8%, with 21 distinct combination patterns identified (support levels: 10.163-14.68%; confidence: 80.39-90.32%). Qi-deficiency frequently coexisted with Yang-deficiency, Blood stasis, Special, Neutral, Qi stagnation, Phlegm-Dampness, and Yin-deficiency.Conclusion: The mixed constitution type (multi-constitution) is prevalent among students of the University of Medicine and Pharmacy at Ho Chi Minh, in which Qi-deficiency acts as a convergence point for various other constitution imbalances.
Keywords: Mixed constitution; single constitution; dominant constitution.